Risiko Usahatani Mangga di Kecamatan Rembang Jawa Tengah - Hendrik Johannes Nadapdap; Bobby Rachmat Saefudin (Jurnal Penelitian Pertanian Terapan, 2020)
Production fluctuation are an indication of production risk. Kragan District is one of the largest producers of mango in Rembang Regency. The production of mangoes produced by Kragan Subdistrict is still relatively low so this research aims to measure the level of risk, find out the factors that influence production and find out the factors that influence the risk of mango production in the Kragan Subdistrict. The object of this study was 31 mango farmers. The measure to calculate the level of risk is the standard deviation and the coefficient variation. The magnitude of the effect of the use of inputs on production risk is analyzed using multiple linear regression with the heteroscedastic method. The results of the calculation of production risk were analyzed using standard deviation and coefficient variation (KV) and having a standard deviation of 66.87 and the coefficient variation is 0.84, this shows that the high chance of production risk in conducting mango farming by 84 percent. Factors that significantly affect the production of mangoes in Kragan Subdistrict are the number of mango trees, organic fertilizers and inorganic fertilizers while the factors that significantly influence the risk of mango production are the number of trees and labor.